PHYTOCHEMICAL SCREENING, TOTAL PHENOLIC CONTENTS AND ANTIOXIDANT ACTIVITY OF CURCUMA PUTII MAKNOI & JENJITT. EXTRACTS - Khongpet, Wanpen; Sanghkawisu, Phontip; Makerd, Watcharasak; Namjan, Maneerat (Life Sciences and Environment Journal, 2023)
Curcuma putii Maknoi & Jenjitt. is a local medicinal plant, found only in Nongbua district, Nakhon Sawan province. This research aimed to study phytochemical screening, total phenolic content, and antioxidant activity of the C. putii Maknoi & Jenjitt. extracts. The phytochemical screening was investigated using the standard method based on color change reaction and precipitation. The total phenolic content was determined using The Folin-Ciocalteu method. The antioxidant activity was tested with the DPPH Radical Scavenging method. The results revealed that C. putii Maknoi & Jenjitt. contained a wide variety of phytochemicals in its various parts. Tannin was found in leaves and had a total tannin content of 325.5 mg/L. The C. putii Maknoi & Jenjitt. extracts showed the highest total phenolic content in leaves (340.89 mg/L). They exhibited inhibition of antioxidants, with a 50% inhibition (IC50) at a concentration of 54.12 mg/mL, compared to the extracts from other parts of C. putii Maknoi & Jenjitt. It could be concluded that leaf extract is highly effective as an antioxidant. Therefore, the proposed plant is an interesting approach for developing healthcare products in future studies.